THE ASSESSMENT OF LEAD CONCENTRATION IN PARTS OF PADDY PLANT AND SEDIMENT FROM SEKINCHAN, SELANGOR - Shaymah, Ramjan (2018)
Oryza sativa, commonly known as rice, is a highly consumed food around the world. Accu-mulation of heavy metals in such a widely used crop is a major concern. Hence, continuous assessments of trace metals are of high importance. This study was conducted to assess the concentration of Pb in different parts of the paddy plant, which were the roots, straw, leaves and grains, and the sediment from Sekinchan, Selangor. The methodology involved acid di-gestion followed by inductively coupled plasma mass spectrometry (ICP-PMS).The quality of the soil was determined by the geoacumulation index (Igeo), enrichment factor (EF) and Maximum Allowable Concentration (MAC). Translocation factor (TF) and bioconcentration factor (BCF) were used to evaluate the uptake of Pb into the plant. Also, the health risk as-sessment was carried out through the calculation of the average daily intake (ADI) and the hazard quotient (HQ). Overall, the quality of the soil was found to be uncontaminated by Pb and the uptake of Pb by the plant was low. The Pb concentration obtained from the samples were decreasing following sediment > roots > leaves > grains > straw. The grains were safe for consumption as the value of ADI and HQ did not show any Pb toxicity